The Teaching Model on Socio-Cultural Diversity: Learning from Indonesian International Kindergarten - Sri Sulastri (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2018)
The socio-cultural diversity of Indonesia often leads to conflicts and disputes. Therefore, education on socio-cultural diversity is needed since early childhood. The kids’ understanding of the concept of diversity would make them care about their presence in their diverse socio-cultural environment. The aim of this research is to describe the education model on socio-cultural diversity applied in early childhood education. This research uses the naturalistic qualitative approach and adopts Spradley’s data analysis technique. The data of this research were obtained from the school foundation, headmaster, teachers, students, and parents in the early childhood education Golden Kids School, Surakarta. The data collection techniques used in this study are an in-depth interview, participative observation, and document analysis. The steps of analyzing the data include writing notes and categorizing the preliminary data, categorizing different themes, making matrix forms, and making a conclusion based on the matrix. The results of the study show that the practice of early childhood education that uses socio-cultural diversity approach through learning materials such as local songs, dances, and folktales from different regions, enables the kids to have the concept of knowledge and attitudes that respect diversity and highly uphold tolerance.